Integration of forage legumes into cereal cropping systems in Vertisols of the Ethiopian highlands - Tedla, A.; Mamo, T.; Gebeyehu, G. (1992)
Field studies were conducted between 1987-1989 at sites on Vertisols at different altitudes in Ethiopia to assess the effects of mixtures of clover undersowings on grain, straw yield and the total biomass production of several wheat varieties. Wheat varieties grown at the medium altitude locations in 1988 and 1989 differed significantly in grain and straw yield; there was no significant grain yield difference among varieties grown at the high altitude locations in 1988. The presence of the clover mixture under wheat did not reduce grain yield significantly across locations and seasons. Undersowing wheat with clover significantly increased the amount of crop residue produced per unit area. In one of the undersowing trials, a study was conducted to investigate the suitable date of planting clover found that early-planted clover germinated and established better than the late-planted ones. There was no significant interaction between the wheat varieties with and without clovers.